Matharpacady-13.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Atmaram is the village mochi (cobbler), plying his trade in the footsteps of his father, who also worked in Matharpacady. His tiny workshop is a hole-in-the-wall located below a staircase at 31 Matharpacady. His customers wait on stools as he goes about repairing their bags and shoes. This is among the rare shops inside Matharpacady, which is otherwise entirely a residential zone.